Quality of Life and Its Associated Factors among Caregivers of Down Syndrome Children - Ponkhoon, Kherlen; Tsogbadrakh, Odgerel; Baatarjav, Bolortungalag; Bayarmagnai, Uranchimeg; Tumurkhuu, Munkhtuya; Jav, Sarantuya (Central Asian Journal of Medical Sciences, 2018)
Objectives: According to the definition by WHO, the quality of life (QoL) is determined by self-evaluation in the community depending on the people’s goal, expectation and standards and the QoL is a result with positive and negative assessments to be measured by the individual aspects. QoL among caregivers of Down syndrome children is not well studied in many developing countries including Mongolia. The aim the study was to evaluate quality of life and its associated factors among caregivers of Down syndrome children. Methods: A community based, cross-sectional study was conducted among 70 caregivers of children with Down syndrome in Ulaanbaatar, Mongolia. Data on QoL was assessed by WHOQOL-BREF questionnaire. Results: About 40% of caregivers considered their QoL good and 54.3% of them considered their health as satisfactory. The mean value of four domains of QoL were slightly different but not statistically (p>0.05). Conclusion: Out of socio-economic indicators, caregivers’ gender, educational level, family income, marital status, number of family members and chronic illnesses of parents and children’s ages have a huge impact on QoL of caregivers. Additionally, environmental self-assessment was directly correlated with assessment of physical health, mental health, and social relation.